Preparation of Quercetin Loaded Microparticles and their Antitumor Activity against Human Lung Cancer Cells (A549) in vitro - Li, Chen; Gao, Liufang; Zhang, Yi; Simpson, Benjamin K. (Current Pharmaceutical Biotechnology, 2019)
Background: Novel quercetin-loaded microparticles (QM) were fabricated using coaxial electrospraying, characterized for surface morphology and release profile, and evaluated for antitumor activity in vitro. Methods: QM exhibited an average diameter of 1.69 ±1.13 mm, which was an appropriate size suitable for respiratory delivery. X-ray diffraction patterns showed that the components in QM existed in an amorphous physical form, leading to favorable interactions between the drug (quercetin), the polymer matrix (polyvinylpyrrolidone, PVP) and other excipients (sodium dodecyl sulfate and sucralose). Results: QM performed much faster release rate compared with free quercetin powder (Q) in vitro. Furthermore, QM also showed more potent inhibitory effects on A549 cell growth with reduced cell viability, decreased cell migration and induced more G0/G1 phase cell cycle arrest than Q. Conclusion: Thus, the quercetin loaded microparticles exhibited more potent inhibitory effects than free quercetin on A549 cell. The increased antitumor activity could be attributed to the enhanced accumulation of quercetin in the A549 cells with the QM. However, further studies are necessary to elucidate the exact mechanisms.
Keywords: fast-release